Synthesis and Characterization of Benzaldehyde Thiocarbohydrazone: Applications in Transition Metal Ion Analysis (International Journal of Food and Nutritional Sciences, 2023)
Benzaldehyde thiocarbohydrazone (BTH) has emerged as a valuable chelating agent in analytical chemistry for the detection and quantification of transition metal ions. This study explores the microwave-assisted synthesis of BTH, offering a streamlined approach with improved yields and reduced reaction times. Comprehensive characterization of the synthesized BTH is performed using various techniques including melting point determination, infrared spectroscopy (IR), nuclear magnetic resonance (NMR) spectroscopy, ultraviolet-visible (UV-Vis) spectroscopy, and thin layer chromatography (TLC). The results confirm the successful synthesis of BTH and provide detailed insights into its structural and functional properties. Furthermore, the study evaluates the application of BTH as a chromogenic reagent for spectrophotometric analysis of metal ions, demonstrating its effectiveness in forming stable, colored complexes. The findings underscore the potential of BTH as a robust and efficient tool for metal ion analysis in diverse analytical contexts.